A Systematic Review: Comparison of triple drug therapy versus double drug therapy for Lymphatic Filariasis - I Gusti Agung Ari Kusuma Yana (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background: Lymphatic filariasis is a parasitic infection caused by nematodes such as filaria Wuchereria bancrofti, Brugia malayi, and Brugia timori. These parasites can be transmitted through mosquito bites such as several species of mosquitoes, particularly Anopheles, Aedes, Culex, and Mansonia with geographical variations in the dominant vector identity. The main strategy used consists of community-wide mass drug administration (MDA) for the entire population at risk to stop disease transmission and prevent infectious morbidity. WHO recommends the use of annual medication in combination with the triple drug ivermectin therapy. Objective: To compare DEC and albendazole (IDA) versus the two drugs albendazole and diethycarbamazine or albendazole and ivermectin therapy. Methods: The literature search was carried out independently by the researcher using the Sciencedirect, Pubmed, and Cochrane online databases without limiting the type of study or the year of publication. The keywords used in this study were combined with the Boolean operator, namely "AND" namely ((((Lymphatic filariasis) AND (albendazole)) AND (diethylcarbamazine)) AND (ivermectin)) AND (compare). Results: Where triple drug therapy was significantly better in reducing and clearing microfilariae and worm nests in patients with lymphatic filariasis compared to two drug therapy alone. However, side effects occur more frequently in the combination of three therapies. The average side effects were low, such as headaches, joint pain, fatigue, and nausea. Conclusion: although it has relatively low side effects that occur in three drug combinations rather than two drug combination therapy, triple therapy combination therapy is more effective than two drug therapy in treating lymphatic filariasis disease.